TO WOMEN’S SEXUALITY IN BREASTFEEDING - Arkan Pedrosa Alves Novo, Rafaela; Michele de Araujo Pedro, Fabiana; Rodrigues dos Santos, Leonardo; da Silva Carvalho, Denise; Carvalho Santana, Fabio; Eloar Rodrigues da Costa, Sinthya; Dias de Faria, Priscila; Oliveira Nascimento Leal Santos, Fernanda (Health and Society, 2023)
The work here focuses on health and society and has a predominant area of Nursing in Women’s Health Care. This is a research with a related theme, the sexuality of women during breastfeeding. The chosen study objects are factors related to the woman’s sexuality that interfere with breastfeeding. Considering that most that most women tend to wean the baby early, this characterizes a low adherence to exclusive breastfeeding and triggers several complications for the NB(newborn) because we know that breast milk has fundamental immune factors for growth and development, being it rich in water, vitamins, proteins, fats and other essential nutrients that prevent disease. Related to the act of breastfeeding, considering that they end up reflecting on social and family life, in addition to the fantasies that are perpetuated in our culture around motherhood and female sexuality, which sometimes sometimes ends up affecting the couple’s relationship, and or the mother-child bond, since the woman confuses the feeling of sexual pleasure she has with her partner with the feeling of breastfeeding the baby.